Metastasis of basal cell carcinoma to lymph nodes in a patient with Gorlin syndrome – case report and literature review - Bajon, Tomasz; Adamiak, Ewa; Krawczyński, Maciej (Contemporary Oncology/Współczesna Onkologia, 2011)
Background : Basal cell carcinoma of the skin is the most common malignant cancer worldwide. It is characterized by a low grade of malignancy and it gives very rare metastases to lymph nodes or internal organs. It is also a typical symptom of Gorlin syndrome, which is characterized by multiple basal cell carcinomas, calcifications in the central nervous system and palmar or plantar pits. Mutations in the PTCH gene are responsible for the development of this syndrome, and its inheritance is autosomal dominant. The estimated frequency of Gorlin syndrome is 1/57 000 – 256 000. Case report : The authors present a case of a 34-year-old man with Gorlin syndrome and metastasis of basal cell carcinoma of the face to the submandibular lymph node. Though there are some reports of high radiosensitivity in patients with this syndrome, in this case postoperative radiation treatment was used. Inter- and post-treatment observation did not confirm an early or late postradiation reaction higher than score 2 on the EORTC/RTOG scale. Within 20 months after the treatment no new malignant lesions of the irradiated skin were noticed. Discussion : In the literature there are fewer than 300 cases of basal cell carcinoma metastases, of which only 3 concern patients with Gorlin syndrome. On the basis of the case presented the authors suggest that early and late radiation toxicity in Gorlin syndrome patients is not as high as previously believed.